التأثير الاليلوباتي لبعض الزيوت الاساسية على إنبات بعض بذور الاعشاب الضارة - مدخل ,وئام; مهري ,عفاف (University of Eloued جامعة الوادي, 2024)
The importance of this research stems from the need to develop environmentally friendly and sustainable solutions for weed control in agricultural fields. Using essential oils as an alternative to chemical herbicides can reduce negative impacts on the environment and public health. In this study, the allelopathic effect of essential oil extracted from Eucalyptus camaldulensis and Salvia officinalis was tested on the germination of selected weed seeds, including Portulaca oleracea, Hordeum vulgare, Medicago sativa, and Coriandrum sativum, growing in a tomato field Solanum lycopersicum L.. The seeds were treated with known volumes of essential oil (20, 40, 100 µl). The results showed total inhibition (100%) of germination of Hordeum vulgare, Coriandrum sativum, and Portulaca oleracea seeds by Eucalyptus oil at all three volumes, while purslane and tomato seeds were less sensitive, especially at 20 µl. Regarding Salvia officinalis oil, there was total inhibition of germination of Hordeum vulgare and Coriandrum sativum seeds, while Portulaca oleracea and Medicago sativa seeds were less sensitive. Tomato (Solanum lycopersicum), seeds were not affected by Salvia officinalis oil, with inhibition reaching 8.95±2.59% at the highest volum
التنوع البيئي و المحيط
Keywords: Allelopathic effect - Essential oil - Eucalyptus Eucalyptus camaldulensis - Salvia officinalis; المريمية - التأثير الأليموباتي- الزيت الأساسي – الأكاليبتوس